Synthesis and in vivo toxicity assessment of CdSe:ZnS quantum dots functionalized with EDTA-Bis-Cysteamine. Issue 5 (31st July 2015) - Bag, Narmada; Mathur, Rashi; Hussain, Firasat; Indracanti, Namita; Singh, Sweta; Singh, Shivani; Chauhan, Ram Prakash; Chuttani, Krishna; Mishra, Anil Kumar
Graphical Abstract: Abstract: The design and surface chemistry of core shell quantum dots significantly affect their bio-distribution, kinetics and toxicity. Bis-ligands have been shown to improve the loading capacity and control the steric ligand packing density on the quantum dot surfaces, thus improving the biological properties and controlling the toxicity of the quantum dot nano-conjugates. In this study, we functionalized core shell CdSe:ZnS quantum dots with a homo-dimeric system (EDTA-Bis-Cysteamine) and evaluated their stability in vivo for diagnostic applications. This homo-dimeric N2 S2 system wraps the quantum dots and has pendant carboxylate moieties for further conjugation chemistry. The novelty in the system is that it can be loaded with a variety of metal atoms through dative bonds, even when the S atoms are attached to the ZnS shell. This results in the formation of a stable complex on a nano-platform for theranostic applications. The synthesized quantum dot nano-conjugate has been structurally evaluated using various analytical techniques. Spectrophotometric studies show the emission of the nano-conjugate at 530 nm, similar to the core shell. The haematology studies, biochemical assays and histopathology performed on the organs of interest showed no significant damage post injection over a time frame of 15 days. The generation of reactive oxygen species by the cadmium based quantum dot nano-conjugate has been evaluated for the first time in vivo using Ferric Reducing Antioxidant Power assay (FRAP). The pharmacokinetics and bio-distribution of the nano-conjugate has been studied using radiolabelling ( 99m Tc). After conjugation, the blood kinetics show increased availability of the quantum dots in the blood pool and the bio-distribution pattern also shows major changes. However, no significant toxic effects were observed during the time scale considered. This study highlights a facile route for designing small homo-dimeric ligand functionalized quantum dots nano-conjugates with favourable biological properties, enhancing their potential to be used as multi-modal imaging/theranostic agents.